The implementation of IFRS in Indonesian Islamic accounting - Agus Arwani (Universitas Hayam Wuruk Perbanas, 2018)
This research examines the IFRS Â implementation in Indonesian Islamic accounting. It employs a literature review method to systematically explain the accounting theory, the Islamic Financial Accounting Standards, and International Financial Reporting Standards (IFRS).Â This study concludes that there is a conflict between the International Financial Reporting Standards (IFRS) and some Islamic principles which has not been yet resolved. The Islamic accounting is also facing some complex issues related to the convergence of International Financial Reporting Standards in Indonesia due to incorrect implementation of IFRS in some countries related to the translation problems from English to local languages. The biggest problem in implementing IFRS convergence for business is dealing with the expenses spent for the development of knowledge, supports and trainings for consultants